Novice chemistry teachers’ instructional strategies in teaching mixed-ability classrooms / Muhamad Furkan Mat Salleh ... [et al.] - Mat Salleh, Muhamad Furkan; Abd. Rauf, Rose Amnah; Mohd Saat, Rohaida; Ismail, Mohamad Hisyam (Universiti Teknologi MARA, 2022)
This qualitative study sought to explore Malaysian novice chemistry teachers' experiences in teaching mixed-ability students during their teaching practicum, focusing on their instructional strategies for dealing with those learners in the class. The researchers employed purposive sampling to select 12 trainee teachers to be involved in semi-structured interviews. The data collected were analysed using the constant comparative method. As a result, two themes emerged regarding participants' instructional strategies: the whole-class approach and adjustment to the learners’ needs. This paper discusses the first theme, which consists of three sub-themes: active learning activities, the use of stimulating learning materials, and assessment practice. Even though novice chemistry teachers primarily engaged mixed-ability students through whole-class instruction, the study found they emphasised active classroom engagement and collaboration between students in their classroom. Besides, they did consider students’ interests and preferences when selecting activities and materials for their lessons. However, the study found that novice teachers mainly did not utilise the data from the formative assessments to inform their decisions in differentiating instruction for mixed-ability learners in class. Though there are differences in students’ ability in class, the teachers generally opted for a ‘one-size-fits-all’ strategy for all students in most lessons. The study recommends that teacher training institutions and related stakeholders provide adequate training for novice chemistry teachers to improve their knowledge and skills in practising differentiated instruction.